A nation fermented : beer, Bavaria, and the making of modern Germany - Terrell, Robert Shea, ca. 20./21.Jh. ca. 20./21.Jh (Oxford University Press, 2024)
How did beer become one of the central commodities associated with the German nation? How did a little-known provincial production standard – the Reinheitsgebot, or Beer Purity Law – become a pillar of national consumer sentiments? How did the jovial, beer-drinking German become a fixture in the global imagination?While the connection between beer and Germany seems self-evident, A Nation Fermented reveals how it was produced through a strange brew of regional commercial and political pressures. Spanning from the late nineteenth century to the last decades of the twentieth, A Nation Fermented argues that the economic, regulatory, and cultural weight of Bavaria shaped the German nation in profound ways. Drawing on sources from over a dozen archives and repositories, Terrell weaves together subjects ranging from tax law to advertising, public health to European integration, and agriculture to global stereotypes. Offering a history of the Germany that Bavaria made over the twentieth century, A Nation Fermented eschews both sharp temporal divisions and a conventional focus on northern and industrial Germany. In so doing, Terrell offers a fresh take on the importance of provincial influences and the role of commodities and commerce in shaping the nation